Clinical development of RET inhibitors in RET-rearranged non-small cell lung cancer: update - Luis Mendoza (Frontiers Media S.A., 2018)
Precision oncology is now the evidence-based standard of care for the management of many advanced non-small cell lung cancers (NSCLC). Notably, new molecular profiling technologies have permitted dynamic growth in the identification of actionable driver oncogenes including RET rearrangements. RET oncogenes cannot be adequately detected by immunohistochemistry, although fluorescence in situ hybridization, reverse transcriptase polymerase chain reaction and next-generation sequencing are complementary diagnostic tools. In the clinical setting, the benefit of the most developed RET inhibitors, i.e., cabozantinb, vandetanib and lenvatinb, in terms of response and median progression-free survival has been demonstrated. The absence of striking clinical results of RET inhibitors underscores the clear need for development of more selective and potent RET inhibitors. This paper reviews the clinical data available on RET inhibitors in RET-associated NSCLC.